W imię miłości. Jeffrey Dahmer i zakochani kanibale - Ancuta, Katarzyna (Er(r)go. Teoria - Literatura - Kultura, 2003)
Katarzyna Ancuta The Things We Do For Love. Jeffrey Dahmer and Cannibal Love Culture The article explores the romantic face of cannibalism. where the act of devouring human flesh is deconstructed as the ultimate expression of love. It focuses on the issue of love cannibalism and the romanticised myth of the loving cannibal. which has been functioning as a successful cultural metaphor since the 1990s. The article sets love cannibalism in the broader context of necrophilia, understood both in terms of a sexual disorder and a morbid fascination with the subject of love in death, Finally, it compares the romantic representation of cannibalism in contemporary texts to the similarly romantic depiction of AIDS, the infection which is treated as equivalent with taking control of the lover's body. The core of the article is the discussion of two criminal cases – Jeffrey Dahmer's and Issei Sagawa's -which serve to illustrate the relationship between love cannibalism and necrophilia. The argument is further expanded to examine various representations of necrophilia and love cannibalism in contemporary literature and film.